Prognostic Accuracy of SOFA Score and qSOFA as a predictor of mortality among sepsis patients presenting to Emergency Department in one of a tertiary Hospital in Kathmandu, Nepal (Nepal Medical College Journal, 2020)
There are many clinical scoring systems that measure the severity in sepsis and septic shock. Therefore, our study aims to calculate prognostic accuracy of commonly used scoring system SOFA and qSOFA in emergency department as a predictor of mortality among sepsis patients.This was prospective observational study conducted in an emergency department for a period of seven months. 156 patients were studied and descriptive statistical analysis was done. The most common source of infection was respiratory. A positive and moderate correlation was seen between initial SOFA score and qSOFA score. The AUC of SOFA score and qSOFA for predicting the mortality were 0.978 and 0.886 with sensitivity of 96.9% and specificty of 57% for SOFA and sensitivity of 96.9% and specificity of 76.1% for qSOFA.SOFA and qSOFA both proved to be similar as a simple prognostic tool with discriminatory capacity in predicting prognosis in septic patient presenting to emergency department.